"They Would Have a Law of Their Own" : The Discourse on Smuggling at the Old Bailey, 1736-1814 - Morrisette, Annie Tock (East Carolina University, 2013)
This thesis examines the cases of 136 men tried for smuggling offenses at London's central criminal court during the long eighteenth century. Before the 1770s, the government portrayed smuggling as a crime against the nation, but after this time, the discourse changed significantly. At a time when smugglers actually were consorting with the enemy, the language of nationalism virtually disappeared from their trials and was replaced by the portrayal of smuggling as a crime of assault against revenue officers. The accounts of smugglers themselves also reveal a shift in emphasis. During the first part of the eighteenth century, smugglers referred to their trade in terms of tradition, and they were surprised to find themselves awaiting execution for such a commonplace activity. But after the 1770s, their language changes, too. Smugglers are increasingly reported to define smuggled goods as their private property and to suggest that revenue officers are in the wrong for seizing what is not theirs by right. This thesis argues that the changes in the discourse reveal both the revolutionary potential of smuggling and the ways authorities sought to change the conversation from one of national import to one of personal assault.
Keywords: Old Bailey; Smuggling--England--18th century; Smuggling--England--19th century; Smugglers--England--18th century; Smugglers--England--19th century; Great Britain--History--18th century; Great Britain--History--19th century; Great Britain. Court of Oyer and Terminer and Gaol Delivery (London and Middlesex)